PENINGKATAN KINERJA GURU MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SDK NGORABOLO - Ase, Maria Conesta (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to improve teacher performance at SDK Ngorabolo through the implementation of academic supervision by the principal. Optimal teacher performance is a key factor in the success of the learning process and the achievement of student learning outcomes. Academic supervision, as part of educational management, plays a crucial role in the professional development of teachers by providing necessary guidance, feedback, and support to enhance teaching quality. The research method used is School Action Research (SAR), which involves cycles of planning, action, observation, and reflection. This study was conducted in two cycles, focusing on classroom observation, feedback provision, and the development of performance enhancement strategies. Data were collected through direct observation, interviews with teachers, and analysis of documents related to lesson plans and student learning outcomes. The results indicate that systematic and continuous academic supervision can significantly improve teacher performance. Assessments showed improvements in several aspects, including lesson planning, classroom management, teaching techniques, and the use of media and learning resources. Teachers demonstrated increased motivation and student engagement as a result of the guidance and feedback provided. The conclusion of this study is that academic supervision by the principal can effectively enhance teacher performance and, ultimately, contribute to the improvement of the quality of education at the school. This study recommends that academic supervision be applied routinely and systematically, involving various aspects of teaching to achieve optimal results.